Women Empowerment in Tamil Nadu Emerging Trends and State Initiatives (Global Journal of Human-Social Science, 2013)
Introduction -Women have had a long history in asserting their rights. It is a commonly accepted view that the male-dominated patriarchal society and power structure would usually keep the position of women low. This powerless situation of women has itself made them to look for a way out and liberation. Reformation thinking, feminist movements, freedom struggle have all contributed in awakening their consciousness. Women empowerment refers to strengthening women's position in social economic and political power structure of the society. It also implies capacity building with the leading role plagued by the State and non-state organizations.
Keywords: structure would usually